Is it ethical to keep interim findings of randomised controlled trials confidential? - Miller, F. G. (Journal of medical ethics, 2008)
Data monitoring committees often are employed to review interim findings of randomised controlled trials. Interim findings are kept confidential until the data monitoring committee finds that they provide sufficiently compelling evidence regarding efficacy, typically because they have crossed the pre-defined statistical boundaries, or they raise serious concerns about safety. While this practice is vital to maintaining the scientific integrity of controlled trials and thereby ensuring their social value, it has been criticised as unethical. Commentators argue that withholding interim findings from research participants is deceptive, inconsistent with valid informed consent, and a violation of respect for participants’ autonomy. The present article examines these arguments, focusing specifically on confidential data monitoring for efficacy. This practice need not be deceptive provided its use is disclosed to prospective research participants. In addition, confidential data monitoring does not make research participants worse off than they would be in the clinical setting and represents an acceptable limitation on the options available to prospective research participants. Taken together, these considerations suggest confidential data monitoring, subject to adequate safeguards, is ethically acceptable.